digiRESCUE: A Smart Personal Emergency Rescue System - Benjamin Kommey; Elvis Tamakloe; Bright Yeboah Akowuah (Department of Electrical Engineering ITS and FORTEI, 2022)
It is of no doubt that, emergencies occur without warning, and one does not predict the outcome. This project seeks to design a personal emergency or panic alert system (digiRESCUE) to aid in inevitable and dangerous situations. The digiRESCUE system has two main parts: the embedded hardware and software application. The hardware part is made up of a button embedded with a chip. This button when pressed triggers the chip, which then activates the software, portion of the system to send an automated message including the individual’s location to the selected contacts saved in the software application. The software part of the system is in the form of a mobile application, which can be downloaded onto a mobile device. This software would allow users to record or write an SOS message and input selected contacts (including friends, family, and authorities) who would be alerted of the user’s predicament when the external button in pressed. This software application can tap into the mobile device’s GPS module to inform the selected contacts of the individual’s location. The hardware would interact with the software application via Bluetooth connectivity therefore making the process of seeking for help, a lot quicker and easier. In situations where the individual is held as a hostage, he or she can easily call for help without drawing attention to oneself